Pengaruh Ekstrak Etanol Bawang Dayak (Eleutherine Bulbosa (Mill) (Urb) terhadap Kadar Glukosa Darah Tikus Wistar yang Diinduksi Streptozotocin - Yaturramadhan, Hasni; Antoni, Adi (Universitas Aufa Royhan, 2019)
Dayak onions (Eleutherine bulbosa (Mill) Urb) contain chemical compounds that have the potential to be antidiabetic. The purpose of this study was to examine the effect of ethanol extract of Dayak onion tubers (EEBD) on blood glucose levels of wistar rats induced by streptozotocin. The method of this study was experimental, as many as 30 diabetic rats were divided into 5 groups with one-day treatment for 14 days: glibenclamide 0 , 25 mg / kg, EEBD 125 mg / kg (BD125); 250 mg / kg (BD250); 500 mg / kg (BD500) and CMC 1% bb (CMC) with evaluations including acute fasting blood glucose (KGD) levels. The result of fasting KGD showed a significant decrease after 7 hours of observation (p <0.001). Statistically this decrease was significantly different compared to the negative group (CMC) (p <0.001). Conclusion EEBD can reduce blood glucose levels.